2017
DOI: 10.1186/s13643-017-0486-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of clinical supervision on supervisees and patients in cognitive-behavioral therapy: a study protocol for a systematic review

Abstract: BackgroundClinical supervision by a senior therapist is a very common practice in psychotherapist training and psychiatric care settings. Though clinical supervision is advocated by most educational and governing institutions, the effects of clinical supervision on the supervisees’ competence, e.g., attitudes, behaviors, and skills, as well as on treatment outcomes and other patient variables are debated and largely unknown. Evidence-based practice is advocated in clinical settings but has not yet been fully i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
2
Order By: Relevance
“…The lack of supervised practice is another challenge. Psychotherapy supervision is defined as a setting in which one psychotherapist instructs and provides training in psychotherapy theories, methods, and skills to psychotherapists while they are treating patients (Alfonsson et al, 2017). In the clinical view, psychiatric nurses do not require CBT supervision because they do not need to implement CBT.…”
Section: )mentioning
confidence: 99%
“…The lack of supervised practice is another challenge. Psychotherapy supervision is defined as a setting in which one psychotherapist instructs and provides training in psychotherapy theories, methods, and skills to psychotherapists while they are treating patients (Alfonsson et al, 2017). In the clinical view, psychiatric nurses do not require CBT supervision because they do not need to implement CBT.…”
Section: )mentioning
confidence: 99%
“…Dialoginiai santykiai supervizijoje ypač akcentuojami egzistencinėje, geštaltinėje, taip pat psichoanalitinėje bei psichodinaminėje paradigmose. O štai kognityvinėje -bihevioristinėje paradigmoje galimas ir "Aš-Tai" santykis, nes kognityvinės -bihevioristinės supervizijos dėmesio centre yra supervizuojamojo mokymas įvairių terapinių technikų ir intervencijų, namų darbų atlikimas ir jų aptarimas supervizijos sesijos metu (Alfonsson et al, 2017;Falender & Shafranske, 2004;Fedoriaka, 2017).…”
Section: Rezultatų Aptarimasunclassified
“…Little is known about how CBT supervision is routinely delivered, monitored or experienced and, given the strong tradition of promoting adherence to research in the field, it is concerning that what little data there are suggests that everyday practices do not always mirror expert recommendations (e.g., Alfonsson et al, 2017; Milne et al, 2009; Townend et al, 2002; Simpson‐Southward et al, 2018; Weck et al, 2017), with key normative, formative and restorative functions often being omitted (Proctor, 1994; Pugh & Margetts, 2020). For example, a study by Weck et al (2017) found that the most widely used method in supervision was case discussion, with limited opportunities to give feedback on the quality of supervisees' clinical work (e.g., video footage of therapy sessions).…”
Section: Introductionmentioning
confidence: 99%